New method of analyzing wave processes in pulse generators based on lines with distributed parameters - Gordeev, V.S. (Вопросы атомной науки и техники, 2001)
A new method of theoretical analysis of wave processes in high-current pulse generators through the relations between integral values reflecting regularities of energy transfer in ideal lines with distributed parameters is described. The use of the method developed considerably simplifies the procedure of searching for an optimal - from the point of view of getting maximal efficiency – relation of impedances for pulse facilities on stepped lines including those with arbitrary number of cascades. High efficiency of the method is demonstrated by several examples.